Effect of using MgO coating with multiple coatings on the optical properties of a five-layer stack - Zainab I. Al-Assadi (مجلة بغداد للعلوم)
A high refractive index (H) 1.7376 dielectric material MgO was used, and four separate low refractive index (L) dielectric materials, BaF2 (Barium fluoride, 1.4825), Al2O3 (Alumina, 1.5322), GdF3 (Gadolinium Fluoride, 1.59) and LaF3 (Lanthanum Fluoride, 1.6056) were added as optical coatings. Five layers across two designs were used for each option. The first format was Glass/H/L/H/L/H, while the second was Glass/L/H/L/H/L. These were tested using MATLAB to calculate the optical properties (M, Rvis., Rsol., and Tsol.) of  the resulting optical coatings were calculated to determine which coating the most efficient for colouring the glass of solar systems used as building façades. The results explained, using the first design, just two coatings were efficient with respect to colouration, with MgO+BaF2 being the most efficient with values of M=8.25 and Rvis=38.2 The MgO+Al2O3 coating was the next most efficient, with values of M=6.12 and Rvis=31.24, the required values for the merit factor (M) and Rvis. which make the coating efficient for colouration are 6% and 12%, respectively. Further, in this case, only one sharp and regular reflection peak of colouration in the visible region was observed. In the first design the refractive index was found to be inversely proportional to the optical properties of the coating, and thus to the colour efficiency of the coating: the MgO+BaF2 coating was thus deemed more efficient than the MgO+Al2O3 coating. The second design was considered inefficient for colouration for all four coatings, as none of these met the required values for (M) and Rvis .